MANTODEA: KOREOGRAFI VISUALISASI SIKLUS HIDUP BELALANG SEMBAH - Agung Yunandi Kristianto; Raja Alfirafindra; Erlina Pantja Sulistijaningtijas (Institut Seni Indonesia Yogyakarta, 2021)
RINGKASANMANTODEA merupakan karya tari yang memvisualisasikan siklus hidup dan gerak-gerik Belalang Sembah dewasa hingga Nimfa (bayi Belalang Sembah). Kata MANTODEA diambil dari ordo mantodea, yang dalam bahasa Yunani berarti satu jenis Belalang Sembah. Gerak-gerik yang dihadirkan dalam karya tari ini adalah simbolisasi sikap Belalang Sembah disaat diam, gerakan merangkak dan gerakan ngoyok kanan dan kiri (badan seperti tertiup angin). Ide koreografi MANTODEA mempunyai keunikan tersendiri. Keunikan tersebut terdapat pada postur tubuh penata tari sendiri yang ternyata mirip Belalang Sembah. Selain kemiripan postur tubuh, penata juga tertarik pada kehidupan Belalang Sembah yang mandiri dan memiliki cinta sejati. Kemandirian disaat menjalani kehidupan. Cinta sejati disaat Belalang Sembah jantan rela mati demi membuahi sel telur. Melalui karya tari ini diharapkan memberikan inspirasi untuk belajar mandiri dan rela berkorban untuk kehidupan selanjutnya.ABSTRACTMANTODEA is the title of this dance work. The concept presented is a visualization of the life cycle and movements of Praying Mantis. The word MANTODEA is taken from the order of mantodea. The order of mantodea adapted from Greek which means one type of praying Mantis. The life cycle that is visualized in this dance work is from adult Mantiss to nymphs (Praying Mantis baby). The movements that are presented in this dance work are symbolic of the attitude of the Praying Mantis while still, crawling movements and movements of the right and left (body like blowing in the wind). The compilation of the MANTODEA choreography is unique. The uniqueness is found in the posture of the dance stylist himself who turns out to be like the Praying Mantis as the main object. Besides the similarity of the same posture the stylist is also interested in his life. The interest of the dance stylist in the life of Praying Mantis is independence and true love. Independence while living life. True love when male locusts are willing to die to fertilize an egg. Through this dance work is expected to be able to learn independently and be willing to sacrifice.